Tracheostomy protocols during COVID‐19 pandemic. Issue 6 (2nd May 2020) - Heyd, Cameron P.; Desiato, Vincent M.; Nguyen, Shaun A.; O'Rourke, Ashli K.; Clemmens, Clarice S.; Awad, Mahmoud I.; Worley, Mitchell L.; Day, Terry A.
Abstract: Background: The COVID‐19 pandemic has resulted in the implementation of rapidly changing protocols and guidelines related to the indications and perioperative precautions and protocols for tracheostomy. The purpose of this study was to evaluate current guidelines for tracheostomy during the COVID‐19 pandemic to provide a framework for health systems to prepare as the science evolves over the upcoming months and years. Methods: Literature review was performed. Articles reporting clinical practice guidelines for tracheostomy in the context of COVID‐19 were included. Results: A total of 13 tracheotomy guidelines were identified. Two were available via PubMed, five in society or organization websites, and six identified via health system websites or other sources. Five were from Otolaryngology‐Head and Neck Surgery specialties, six from Anesthesiology and one from Pulmonary/Critical Care. All (100%) studies recommended postponing elective OR cases in COVID‐19 positive patients, while seven recommended reducing team members to only essential staff and three recommended forming a designated tracheostomy team. Recommendations with supporting references are summarized in the article. Conclusions: Tracheostomy guidelines during the COVID‐19 pandemic vary by physician groups and specialty, hospital systems, and supply‐chain/resource availability. This summary is provided as a point‐in‐time current state of the guidelines for tracheotomy management in April 2020 and is expected to change in coming weeks and months as the COVID‐19 pandemic, virus testing and antibody testing evolves.